Immune mediated myasthenia gravis in children, current concepts and new treatments: A narrative review article - Tavasoli, Azita (Iranian Journal of Child Neurology, 2024)
Myasthenia gravis (MG) is the most frequent transmission disease in the neuromuscular junction. Juvenile myasthenia gravis (JMG) is an autoimmune antibody-mediated disease of postsynaptic endplate defined as MG presentation in patients before the age of 18 years old. While many clinical features of JMG are identical to the adults, there are some significant differences between them regarding presentation, clinical course, antibody level, and thymus histopathology. In JMG, ocular symptoms are more frequent, the clinical course is comparably benign, and the outcome is better than adult MG. Antibodies attack the muscle endplate proteins in the postsynaptic membrane and interfere with transmission. These antibodies in most patients are against the acetylcholine receptors, but they may also be directed toward muscle-specific kinase, lipoprotein-related protein 4, and agrin. Findings show racial influences and genetic effects on the occurrence of JMG. The essential clinical symptom is fatigable weakness of muscles that can be in the form of isolated ocular type or more disseminated weakness. The diagnosis of JMG is essentially clinical, with fluctuating patterns of weakness and easy fatigability, but a series of diagnostic evaluations can confirm the diagnosis. Precise diagnostic evaluation and distinction from congenital myasthenic syndromes is critical. The treatment plan is conducted according to the clinical course (ocular or generalized), antibody type, and disease severity. The mainstay of treatment includes symptomatic therapy, long-lasting immunosuppressive treatment and treatment of myasthenic crisis. Novel medications are introduced and conducted to the specific pathophysiologic mechanisms of the disease, and they are used primarily in the refractory MG.